Reduction of inflammatory slan (6-sulfo LacNAc) dendritic cells in psoriatic skin of patients treated with etanercept - Günther, Claudia; Blau, Kristin; Förster, Ulrike; Viehweg, Antje; Wozel, Gottfried; Schäkel, Knut (Experimental dermatology, 2013)
Dermal dendritic cells (DCs) play a central role in the immunopathology of psoriasis. We previously identified slanDCs as pro-inflammatory TNF-α, IL-23- and IL-12-producing DCs in human blood and as prominent inflammatory dermal TNF-α secreting and CD11c-positive DC subset in psoriasis. Here, we ask for the effects of TNF-α-inhibition on inflammatory slanDCs in skin and blood of 10 patients with psoriasis during 24 weeks of treatment with etanercept. Treatment with etanercept reduced the frequency of dermal slanDCs but did not induce apoptosis as determined by lack of increased active caspase-3-expression. In parallel, we found increased frequencies of slanDCs in blood which expressed lower levels of HLA-DR. Stimulating slanDCs isolated from the blood of healthy donors in vitro induced a strong production of IL-1β, IL-6, IL-23 and IL-12p70. This capacity was efficiently reduced in the presence of etanercept, thereby indicating that TNF-α is an autocrine stimulus for maturation and pro-inflammatory cytokine production of slanDCs. In vivo, we noticed that treatment with etanercept did reduce the number of dermal slanDCs in parallel to the overall expression of TNF-α and IL-23p19. However, successful treatment did not down-regulated the percentage of dermal slanDCs that stained positive for TNF-α and IL-23p19 indicating that remaining slanDCs kept their pro-inflammatory capacity. This study provides novel insights into the immune regulatory properties of etanercept at the level of inflammatory slanDCs in vivo in skin and blood as well as in vitro.
Gesehen am 11.02.2021